Identifikasi dan Estimasi Kadar Mineralisasi Uranium Secara Kuantitatif Berdasarkan Log Gross-Count Gamma Ray di Sektor Lemajung, Kalimantan Barat - Muhammad, Adi Gunawan (EKSPLORIUM, 2014)
Lemajung sector, is one of uranium potential sector in Kalan Area, West Kalimantan. Uranium mineralization is found in metasiltstone and schistose metapelite rock with general direction of mineralization east-west tilted ± 70⁰ to the north parallel with schistocity pattern (S1). Drilling evaluation has been implemented in 2013 in Lemajung sector at R-05 (LEML-40) with total depth of 300 meters and has been completly with well-logging by gross-count gamma ray. The purpose of this activity is to determine uranium mineralization grade with quantitatively methode in the rocks and also determine the geological conditions in sorounding of drilling area. The methodology involves determining the value of k-factor, geological mapping for the sorounding of drill hole, determination of the thickness and grade estimation of uranium mineralization with gross-count gamma ray. Quantitatively from grade estimation of uranium using gross-count gamma ray log can be known that the highest % eU3O8 in the hole R-05 (LEML-40) reaches 0.7493≈6354 ppm eU found at depth interval from 30.1 to 34.96 m. Uranium mineralization is present as fracture filling (vein) or tectonic breccia matrix filling in metasiltstone with thickness from 0.10 to 2.40 m associated with sulphide (pyrite) and characterized by high ratio of U/Th.